Menemukan Diri Lewat TikTok: Mengeksplorasi Potensi Kreatif Anak dengan Down Sindrom - Antika, Mega Windi; Kholifah, Umi Nur; Indriani, Tia (unprimdn.ac.id, 2023)
Self-disclosure or self-disclosure for the millennial generation is an effective way of trying to achieve self-existence, finding self-identity and as a means of communication and information for others. TikTok is one of the media used to reveal one's identity. This article aims to provide an overview of the social interactions that occur in children with Down syndrome with the community through social media. this study used qualitative methods with a literature and library approach. The results of this study indicate that the Internet provides convenience in terms of communicating and interacting with others. man. Social media, which uses internet technology, is an alternative medium for expressing identity for its users. TikTok is a social media that can provide space for its users to express their identity so that they are better known and get the attention of other users. Self-disclosure in children with Down syndrome through social media, namely Tiktok, is very useful for improving the quality of social interaction and social support for children with Down syndrome in developing their interests and talents on social media.